Table of Content - - (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content: 1. Mentioning of the Righteous and the Wicked in Surat Al-Mutaffifin in the Quran; An Analytical Rhetorical Study Dr. Meshal Fehan Ballash Al-Osaimi 2. The extent of the legitimacy of Arab peace treaties with the Zionist enemy entity in Islamic law and man-made legislation Mr. Hameed Aadm Ali Qushaimh 3. The effectiveness of an educational unit to develop students’ skills in designing fashion shows using virtual reality and its impact on electronic shopping in Asir region, Saudi Arabia Dr. Randa Mounir Elkherbaway, Dr. Samar Ahmed Kanona , Dr. Ngawha Kamel Bosiala 4. Introducing innovative designs for horse riding clothing for women in the Kingdom of Saudi Arabia Mrs. Abrar Hashim Alattas , Co-Prof. Hana Abdullah Alamodi 5. From natural translation to translation competence: Pedagogical implications Mrs. Habiba Nakhli 6. E-Marketing of Information Services in Yemeni Private University Libraries in Sana’a City Dr. Samar Gamal Al-Habbari